Czech (Paliativní medicína, 2024)
The article attempts to define spirituality in a way that corresponds to the Central European understanding. It presents three narrative categories that patients use when talking about their spirituality. It addresses the question of possible measurement of spirituality. Highlights research that describes the impact of spirituality on patients' well-being. Finally, it reconstructs possible coping strategies and their sources based on this research.
Keywords: spirituality, coping, patient well-being, construction of life